The impact of cultural values, security perceptions, and influencer interactions on social commerce adoption in Indonesia - Sabirin , Sabirin; Elliyana, Ela; Rosmiati , Rosmiati (Global Academy of Business Studies, 2024)
Purpose: This study aims to analyze the influence of local cultural values, perceived security and privacy, consumer–influencer interactions, the use of social commerce, and marketing strategies through social media on social commerce adoption in Indonesia. The transformation from e-commerce to social commerce has reshaped consumer behavior, emphasizing trust, engagement, and cultural adaptation on digital platforms. Methods: A quantitative approach was applied using an online questionnaire distributed to 300 respondents in Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate the relationships among cultural, behavioral, and technological factors influencing social commerce adoption. Results: The findings confirm that All five hypotheses were accepted. Local cultural values, perceived security and privacy, influencer interaction, social commerce usage, and social media marketing strategies significantly affect adoption and usage. Perceived security and privacy enhance consumer trust, influencer interaction fosters engagement, and social media marketing increases purchase intention. Conclusion: This study concludes that cultural adaptation, trust-building, and interactive marketing are key to strengthening consumer engagement and adopting social commerce in Indonesia. Limitation: This study is limited to a cross-sectional dataset of Indonesian respondents and does not capture longitudinal changes or regional variations in consumer behavior. Contribution: This study enriches the understanding of digital consumer culture by integrating sociocultural and technological perspectives, offering practical insights for businesses to develop culturally adaptive and trust-oriented social commerce strategies.